Morphysiological-behavioral evaluation of several tobacco (Nicotiana tabacum L.) varieties under the influence of drought stress induced with polyethylene glycol (PEG-6000) (Latakia University Journal -Biological Sciences Series, 2023)
The experiment was carried out in the scientific research laboratory (Tishreen University/Faculty of Agricultural Engineering) during the agricultural season (2022). Drought stress induced with polyethylene glycol (PEG-6000) concentrations (0-5-10-15-20) % was applied, by using seedlings of three tobacco varieties (Virginia VK51- Burly 21- Katrina), that were grown in glass containers (1 Liter capacity) containing a nutrient solution (Auckland), which was prepared in a laboratory. The experiment was designed according to a complete randomized design (RCD) with three replicates per treatment. The research aimed to study the behavior of the varieties used under the influence of drought stress and to determine the most stressful concentrations. So, a number of morphysiological characteristics as plant height (cm), total leaf area (cm2), net photosynthesis rate (g/cm2/day) and total content of chlorophyll and carotenoids (µg/g fresh weight) were measured. The results showed a stimulating effect of drought stress applied at 5% PEG-6000, which was noticeable in plant height and leaf area of the three varieties. As for the rest of the traits, the applied drought stress led to a significant decrease in the net photosynthesis rate and the content of chlorophyll and carotenoids compared to the control in the three varieties. The research concluded that Katrina variety was more stress-tolerant at the highest concentration 20% PEG-6000, followed by Burly 21 and Virginia VK51, due to the decrease by about 50-71-96 and 31-38-40% in net photosynthesis rate and total leaf area, respectively, compared to the control for each variety.